A bilateral cyano molecule serving as an effective additive enables high-efficiency and stable perovskite solar cells - Liu, P.; Xiang, H.; Wang, Wei; Ran, R.; Zhou, W.; Shao, Zongping (ELSEVIER, 2021)
The existence of defects in perovskite films is a major obstacle that prevents perovskite solar cells (PSCs) from high efficiency and long-term stability. A variety of additives have been introduced into perovskite films for reducing the number of defects. Lewis base-based additive engineering has been considered as an effective way to eliminate defects, especially the defects caused by the uncoordinated Pb2+. In this work, for the first time, a bilateral cyano molecule (succinonitrile, SN) which is a commonly used plasticizer in solid electrolyte of solid-state lithium batteries was selected as an additive to modify organic–inorganic hybrid perovskite films in PSCs. SN is featured with two cyano groups (–C≡N) distributing at both terminals of the carbon chain, providing two cross-linking points to interact with perovskites crystals via coordinating with uncoordinated Pb2+ and forming hydrogen bonds with –NH2 groups in perovskite. It was found that the addition of SN into perovskite precursor solution could effectively reduce defects, particularly inhabit the appearance of Pb0 and thus suppress trap-assisted nonradiative charge carrier recombination. As a result, the efficiency of CH3NH3PbI3(Cl) (MAPbI3(Cl))-based PSCs was improved from 18.4% to 20.3% with enhanced long-term stability at N2 and humid air atmosphere. This work provides a facile and effective strategy to enhance the PCE and stability of PSCs simultaneously, facilitating the commercialization of PSCs.